Արիանոսի մի տեղեկության շուրջ - Հովհաննես Խորիկյան (ՀՀ ԳԱԱ հրատ.)
Одно из сведений греческого историка II века нашей эры Арриана об участии армян в битве при Гавгамелах в 331 г. до н. э. стало причиной разных толкований в арменоведении. Историк пишет, что во время битвы при Гавгамелах «над армянами начальствовали Оронт и Мифравст». Сравнение сведений Арриана и других античных авторов показывает, что вышеупомянутый в битве при Гавгамелах Оронт был сатрапом Армении, а Мифравст – гиппархом Пактиике, находящегося западнее Евфрата. One of the testimonies of the Greek historian Arrian of the 2nd century AD referring to the participation of Armenians in the Battle of Gaugamela gave rise to various disagreements in Armenology. The historian writes that in the Battle of Gaugamela “Armenians were lead by Orontes and Mithraustes”. The comparison of the evidence by Arrian and other ancient authors shows that Orontes mentioned in the Battle of Gaugamela was the Satrap of Armenia, and Mithraustes was the Hyparch of Pactyica spreading to the west of the Euphrates.
Keywords: History; Ancient History; D History